The effect of remote peer support on stigma in patients after breast cancer surgery during the COVID-19 pandemic: A protocol for systematic review and meta-analysis. Issue 24 (18th June 2021) - Liang, Dandan; Jia, Ruiying; Yu, Jingfen; Wu, Zhen; Chen, Chaoran; Lu, Guangli
Abstract: Background: Patients after breast cancer surgery have a high sense of stigma due to the formation of surgical scars, loss of breast shape or other reasons, leading to anxiety, depression, and other adverse mental health problems, thus reducing their quality of life. Remote peer support intervention based on telephone, internet or email is low-cost and easy to spread, and protects patients' privacy, solves the barriers to access that many patients face when attending face-to-face programs. Therefore, remote peer support may be an effective way to reduce stigma and improve mental health in patients after breast cancer surgery during the coronavirus disease 2019 (COVID-19) pandemic. Methods: Eight databases (PubMed, Embase, Cochrane Library, CNKI, PsycNET, MEDLINE, Psychology & Behavioral Sciences Collection and Web of Science) will be used to select eligible studies that were published from inception to May, 2021. The eligible studies will be screened, extracted and then the methodological quality will be evaluated independently by 2 reviewers. Review manager software version 5.3 software and Stata version 14.0 software will be used for meta-analysis. Results: The results of this study will show the effect of remote peer support on stigma, depression and anxiety in patients after breast cancer surgery during the COVID-19 pandemic and will be submitted to a peer-reviewed journal for publication. Conclusion: The results of this study will provide evidence for the effectiveness of remote peer support in patients after breast cancer surgery during the COVID-19 pandemic. PROSPERO registration number: CRD42021255971.